Models of Agustín Moreto’s influence in Europe: two Nineteenth-Century English reworkings of El desdén, con el desdén (Castilla. Estudios de Literatura, 2026)
This paper analyses two 19th-century English reworkings of Agustín Moreto's comedy El desdén, con el desdén, written by George Hyde and John Westland Marston: Love's Victory or The School for Pride and Donna Diana. The aim of this study is to demonstrate the richness of Moreto's influence in Europe, as well as the complexity of the intertextual networks woven around it over the centuries, as foreign rewriters turned to various previous versions of the play for the composition of their texts.
Keywords: Golden Age theatre; European theatre; nineteenth century; Agustín Moreto; George Hyde; John Westland Marston